Sistematização do processo de redesenho de poltronas para ônibus intermunicipais - Walber, Márcio (2003)
This work has its basis on the “act of designing”, one of the most important tasks of Engineering, that has a vital attribution in our society, considered nowadays so modern and advanced, applying solutions to attend the human necessities, mainly the ones that can be satisfied by technological factors of our culture. The topic of this work is the systematization of a method to redesign the highway buses intercities, specifically the ones that take short and not so long trips, with the goal to keep the passenger comfortable, once to spend a long time sitting in a not ergonomic position can cause health problems like lumbar pains and spine degeneration. Many factors have been attributed to these risks, from the formal conception of the seats out of ergonomic standard until the kinds of materials applied over their structures. The main goal of this work is to present the use of a method to redesign the highway buses seats, mainly the ones that are used to intercities trips. The secondary goals are: a) to became people involved in product project aware about the importance of project drawing; b) to show some solutions of comfort and new technologies, seeking after the product improvement; c) to recompose the history from the arising of this mean of transportation until its evolution; d) to identify formal and functional problems, indicating improvements to the product in these aspects; e) to propose support to redesign new seats. The methodology used to redesign this product follows the traditional basis of industrial draw, one of the most important contribution of this work is to register this method to help people who want to apply it in seats projects or similar products.